Answer:
x= 7
Step-by-step explanation:
1st step: Multiply the factor (outside number) with the numbers and variable(s) in the box. This results in 2(x-3) = 2x-6
2nd Step: continue the rest of the equation since there are no more brackets left so 2x-6-12=-4
3rd Step: send -12 to the other side of the equation (side changes sign changes) so it will become 2x-6=-4+12 (You are actually supposed to make the variable alone on one side of the equation so that you would be able to calculate its value)
4th step: 2x-6=8 ---> send -6 to the other side as well which will then result in 2x=14
5th step: since 2 is being multiplied by x, when you send it to the other side (to make x alone) you will divide 14 by 2 ( sign of 2 changes from multiplication to division)
Final Step: x=7
Answer:
c. (x+3)(x+9)
Step-by-step explanation:
x^2+12x+27
The middle number is 12 and the last number is 27.
We need two numbers that...
Add together to get 12
Multiply together to get 27
Try 3 and 9:
3+9 = 12
3*9 = 27
Fill in the blanks in
(x+_)(x+_)
with 3 and 9 to get...
(x+3)(x+9)
That relaton i a function
The value of the 24th term is 16.
<h3>Arithmetic progression:</h3>
where
a = first term
d = common difference
n = number of terms
Therefore,
6 = a + 3d
8 = a + 7d
let's find a and d
2 = 4d
d = 2 / 4
d = 1 / 2
6 = a + 3 / 2
a = 6 - 3 /2
a = 4.5
Therefore, the 24th term can be found as follows;
24th term = 4.5 + 23(0.5)
24th term = 4.5 + 11.5
24th term = 16
learn more on arithmetic progression here; brainly.com/question/9882454